(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The study used a physical method, namely laser modification, in addition to chemical treatments, to produce Wet-Blue leather semi-finished products. Laser treatment accelerates the formation of reactive radicals by opening various bonds in the skin tissue, and during subsequent treatment, these reactive radicals and chromium-containing complex compounds enter into a chemical reaction. It was confirmed that the Wet-Blue sheepskin leather semi-finished product has improved physical and mechanical properties when treated with laser light before tanning. The tensile strength was found to be 25.0% higher than that of the Wet-Blue sheepskin leather semi-finished product produced using traditional technology.